SISTEM INFORMASI GEOGRAFIS PERSEBARAN PRODUKSI PADI DI KABUPATEN KEBUMEN TAHUN 2017 DAN 2018 - Bara Setiajati Abdullah (Adisam Publisher, 2024)
Kebumen Regency is one of the regencies that has abundant potential food resources. Submission and presentation of information regarding rice production results by BPS Kebumen Regency is still in catalog form and not yet in mapping form. Based on this, it is deemed important to design and build a